Optimizing IT Infrastructure by Virtualization Approach - Thomas Budiman; Jarot S. Suroso (IAES Indonesia Section, 2016)
The goal of this paper is to get the best potential configuration which can be applied to a physical server without compromising service performance for the clients. Data were compiled by direct observation in the data center observed. Data was then analyzed using the hermeneutics approach to understand the condition by textual data gathered understanding. The results would be the best configuration for a physical server which contains several virtual machines logically separated by its functions. It can be concluded that indeed one physical server machine can be optimized using virtualization so that it may deliver the peak performance of the machine itself and the impact are throughout the organization.